Proceedings of the 1st ACM International Health Informatics Symposium 2010
DOI: 10.1145/1882992.1883034
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and estimating the spatial distribution of healthcare workers

Abstract: This paper describes a spatial model for healthcare workers' location in a large hospital facility. Such models have many applications in healthcare, such as supporting timeand-motion efficiency studies to improve healthcare delivery, or modeling the spread of hospital-acquired infections. We use our model to estimate spatial distributions for healthcare workers in The University of Iowa Hospitals and Clinics (UIHC), a 700-bed comprehensive academic medical center spanning a total of 3.2 million square feet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…One of the questions we wanted to answer was whether knowing when workers visit rooms can be enough to predict their interactions (i.e., close proximity contacts). In a sense, this work was meant to validate previous work done in the compepi group in which contacts between healthcare workers were estimated by the spatial and temporal proximity of their respective computer logins, creating login networks [18,17,16]. We confirmed this hypothesis by being effectively able to predict contacts from visits to rooms.…”
Section: Predicting Interactions From Room Visitssupporting
confidence: 69%
See 2 more Smart Citations
“…One of the questions we wanted to answer was whether knowing when workers visit rooms can be enough to predict their interactions (i.e., close proximity contacts). In a sense, this work was meant to validate previous work done in the compepi group in which contacts between healthcare workers were estimated by the spatial and temporal proximity of their respective computer logins, creating login networks [18,17,16]. We confirmed this hypothesis by being effectively able to predict contacts from visits to rooms.…”
Section: Predicting Interactions From Room Visitssupporting
confidence: 69%
“…Due to the unavailability of data, early studies used synthetic network models to study the spread of infection [79,56,78]. In spite that contact network epidemiology was proposed more than 30 years ago [45], it has been only in the recent years (mostly since 2011) that research groups started measuring detailed contact network data to study the transmission of infection [118,50,5,74,59,4,75,120,36,19,60], an effort joined by the compepi group [18,17,102,81,48,82,16,83].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that healthcare workers are main transmitters of diseases and shall be vaccinated with a higher priority. Curtis et al [34] modeled dynamic contact networks by deriving spatial distributions of healthcare workers and generating random walks to predict human movements in a hospital. Prakash et al [15] constructed a time-varying network which follows an alternating connectivity behavior to model the day-night pattern of nurse shifts and derived a closed-form equation for the epidemic threshold with their network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent work suggests that healthcare worker contact graphs may indeed exhibit small world properties [61,29,28], so in this thesis we tend, in the limit, towards agentbased infectious disease simulations (e.g., one compartment for each agent in the simulation rather than one compartment for the entire population). We find that healthcare worker contact networks based on our agent-based simulator do indeed exhibit classic "small world" properties [117,87], and thus agent-based simulation is critical for understanding and controlling the spread of hospital-acquired infections such as "Clostridium difficile" (C. diff), methicillin-resistant "Staphylococcus aureus" (MRSA), or vancomycin-Resistant "Enterococcus" (VRE).…”
Section: Applications For a Hospital Simulatormentioning
confidence: 99%